2006
DOI: 10.1080/00480169.2006.36720
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular and sublingual sialocoeles in the dog: A retrospective evaluation of 41 cases, using the ventral approach for treatment

Abstract: Excellent clinical results were achieved with a low rate of complications using the ventral approach for mandibular and sublingual sialoadenectomy. The ventral approach is recommended to minimise the risk of recurrence of sialocoeles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
96
2
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(118 citation statements)
references
References 7 publications
4
96
2
16
Order By: Relevance
“…This approach allows better exposure and excision of the entire complex and although it is technically more demanding than the lateral approach no recurrences have been reported (Lane , Ritter et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This approach allows better exposure and excision of the entire complex and although it is technically more demanding than the lateral approach no recurrences have been reported (Lane , Ritter et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Tunneling under the digastricus muscle increased exposure and facilitated complete removal of these lobules in 13 of 15 procedures. Previous studies have demonstrated that mucocele formation most often occurs as a result of a defect in the rostral portion of the polystomatic sublingual gland/duct complex, and that recurrence is commonly attributed to incomplete removal of the rostral salivary tissue or failure to remove the site of rostral duct rupture . Therefore, by allowing for the removal of most, if not all additional salivary tissue, tunneling appears to offer specific advantages over a conventional lateral approach to the mandibular and sublingual salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 most common sites of saliva accumulation are the intermandibular region (cervical mucocele) and under the tongue at the base of the lingual frenulum (sublingual mucocele or ranula) . Salivary mucoceles have been reported to result from trauma, foreign bodies, sialoliths, mucus retention, neoplasia, and recent oral surgery; however, in most cases no inciting cause is identified …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is the treatment of choice for sialoceles and requires complete excision of the involved gland‐duct complex to be curative . Recurrence of sialocele after surgery occurs in between 5 and 14% of cases.…”
mentioning
confidence: 99%